PENGARUH MODAL KERJA, PERPUTARAN PIUTANG, DAN TOTAL HUTANG TERHADAP LABA BERSIH: Studi Empiris Pada Perusahaan Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Oktapianus Oktapianus; Syamsul Mu’arif (Bussman Journal : Indonesian Journal of Business and Management, 2022)
This study aims to provide empirical evidence of the effect of Working Capital, Accounts Receivable Turnover and Total Debt on Net Profit in food and beverage sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This type of research is quantitative research. The type of data used is secondary data. The research sample was taken using purposive sampling technique. The total data obtained is 55 data. Data analysis technique using multiple linear regression analysis. Data processing using Eviews 9. The results of this study indicate that Working Capital, Accounts Receivable Turnover, and Total Debt simultaneously affect Net Profit. The results of the study partially show that Working Capital and Total Debt have an effect on Net Profit, while Accounts Receivable Turnover partially has no effect on Net Profit